2010
DOI: 10.1007/s00384-010-1028-0
|View full text |Cite
|
Sign up to set email alerts
|

CARD15 mutations and colorectal cancer in a South European country

Abstract: Purpose CARD15 mutations are associated with higher susceptibility to Crohn's disease (CD) and longstanding colonic CD increases the risk of developing colorectal cancer (CRC). The relation between these mutations and sporadic CRC remains controversial. The aim of this study was to assess whether germline and/or somatic CARD15 mutations are risk factors for sporadic CRC in Portugal and whether there are genotype-phenotype correlations in these patients. Methods The three main CARD15 mutations (R702W, G908R and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
(90 reference statements)
2
9
1
Order By: Relevance
“…For Hungary, the main factor may be the insufficiency of sample size in the investigation of Lakatos et al [69]; for Poland, the major factor is obscure; and other possible reasons for these disparities may be similar to those that were suggested above for the rs2066847 polymorphism. As in the case with rs2066847, the similar age-dependent influence of the rs2066844 polymorphism on the CRC risk (higher in patients older than 50 -60 years) was detected in German [72] and Portuguese [75] populations.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…For Hungary, the main factor may be the insufficiency of sample size in the investigation of Lakatos et al [69]; for Poland, the major factor is obscure; and other possible reasons for these disparities may be similar to those that were suggested above for the rs2066847 polymorphism. As in the case with rs2066847, the similar age-dependent influence of the rs2066844 polymorphism on the CRC risk (higher in patients older than 50 -60 years) was detected in German [72] and Portuguese [75] populations.…”
Section: Introductionsupporting
confidence: 55%
“…For rs2066845 and rs2066844, results are also conflicting in different populations. Positive results were obtained in a Greek population [64] for rs2066845 polymorphism and in Greek [64], New Zealand [66], German [72] and Portuguese [75] populations for rs2066844 polymorphism. Nevertheless, in Finnish [63,68], Hungarian [69], and Polish [70,71] populations results for both of them were negative.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The NOD2 polymorphism GG (rs rs9302752) was associated with a higher frequency of lymph node metastases. NOD2 polymorphisms were previously associated with colorectal cancer risk [29], although Wex et al [30] did not find NOD2 genetic variants to be a risk factor for gastric carcinogenesis in a Caucasian population. In the present study, no association was found between NOD2 or TLR10 polymorphisms and bladder cancer risk.…”
Section: Discussionmentioning
confidence: 99%